2018
DOI: 10.1016/j.jiph.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Mutations inside rifampicin-resistance determining region of rpoB gene associated with rifampicin-resistance in Mycobacterium tuberculosis

Abstract: Molecular methods which can identify extensive mutations associated with multiple anti-tuberculous drugs are in urgent need so that the research on drug resistant mutations should be extended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
127
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 29 publications
7
127
1
1
Order By: Relevance
“…In RRDR, the most commonly mutated codons are 512, 513, 516, 526, 531. In addition, mutations outside RRDR were also detected in Rif-resistant strains (Zaw et al, 2018). In this study, we found that A650 and L4650 strains had changes in the codon in RRDR (Gln513Pro, Val524Ile).…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…In RRDR, the most commonly mutated codons are 512, 513, 516, 526, 531. In addition, mutations outside RRDR were also detected in Rif-resistant strains (Zaw et al, 2018). In this study, we found that A650 and L4650 strains had changes in the codon in RRDR (Gln513Pro, Val524Ile).…”
Section: Discussionmentioning
confidence: 62%
“…The full-length of the rpoB gene was 4029 bp encoding a polypeptide with 1342 amino acids (Campbell et al, 2001). Mutations in the rpoB gene were found to be associated with Rif resistance of some bacterial strains such as Mycobacterium tuberculosis, Escherichia coli, Acinetobacter baumannii, Bacillus subtilis, V. parahaemolyticus (Hazen et al, 2009;Jin and Gross, 1988;Maughan et al, 2004;Perez-Varela et al, 2017;Zaw et al, 2018), and the mutation position would affect the level of the resistance to Rif (Taniguchi et al, 1996). Hazen et al (2009) reported that V. parahaemolyticus Rif-resistant strains with concentration at 100 µg/ml had the mutations in the rpoB gene (Hazen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations